The reflection of the pandemic experience in contagion (an operant conditioning theory criticism) - Mister Gidion Maru; Sergio Reanaldy Mantouw; Fivy Andries (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
This study aims to analyze the reflection on the pandemic circumstances and on the attempts to solve such turmoil as portrayed in the film entitled Contagion. As a sort of literary criticism, this study is qualitative in design. Data collection deals with the use of transcript of the speeches and actions of the characters in particular scenes and certain minutes. For data analysis, this study applies a kind of psychological approach especially Skinner’s Operant Conditioning Theory as means of doing the analytical criticism on the film. The analysis results in the findings such as Contagion illustrates the occurrence of the pandemic as indicated by the presence of the pandemic, its victim and spread. Further, the study also reveals that solution for the pandemic can be performed by the government, society, and individual. This study seems to be significant to inspire and encourage solution for the current pandemic condition.